ANALYZING THE CUSTOMER PREFERENCES ON KARAOKE SERVICE IN MANADO (STUDY AT INUL VIZTA KTV AND DIVA KARAOKE) - Lembong, Monica (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Entertainment is become customer needs in these days. The number of customer of Karaoke Service has grown rapidly over the past years. This potential market growth resulted in increased competition. To compete, a company has to design strategies that match with the company resources and opportunities in the competition. The purpose of this research is to determine which criteria in karaoke service is mostly selected by user and to define the strengths for each karaoke service captured by user based on the criteria developed in Analytical Hierarchy Process. This research used Analytical Hierarchy Process (AHP) to compare each karaoke service based on service quality, social factor, facility and price. The samples of this research are Inul Vizta KTV and DIVA Karaoke. To ensure the accuracy of the analysis, this research use expert choice 11 to process the data from respondents. The result of this research discovered that price is the main consideration of customer in order to choose Karaoke with average value 0.340 followed by social factor 0.309 and service quality 0.230. This means each karaoke service has to focus on their price strategy to attract customer since price is the priority criteria as consideration for customer to choose karaoke service. Keywords: service quality, social factor, facility, price